Desorption measurements of accelerator-related materials exposed to different stimuli. (December 2021) - Velthaus, V.; Tietz, B.; Trautmann, C.; Völklein, F.; Bender, M.
Abstract: High-energy particle accelerators require low desorbing components to minimize beam-induced pressure rises leading to serious beam intensity losses. To better understand the specific mechanisms of desorption and outgassing processes, a new UHV setup was developed that allows us to apply different stimuli such as temperature, electrons and energetic ions. The different stimuli probe different sample depths and enable the identification of surface and bulk contributions. Data on thermal desorption spectroscopy (TDS) and electron-stimulated desorption (ESD) are presented for a series of pure metals, stainless steel and gold-coated copper samples. TDS experiments with ex-situ preannealing at 400 °C under UHV conditions for about 4 h indicate that this procedure is most appropriate to significantly reduce bulk-related desorption. Highlights: A new UHV setup for desorption measurements with different stimuli (thermal, electrons, ions) is presented. Reduced gas desorption by ex-situ thermal annealing at 400 °C in UHV environment. For thermal desorption bulk properties play a significant role.